ChemInform Abstract: Synthesis of Tetra‐Substituted 5‐Trifluoromethylpyrazoles via Sequential Halogenation/Palladium‐Catalyzed C—C and C—N Cross‐Coupling. Issue 25 (June 2016) - Wiethan, Carson; Rosa, Wilian C.; Bonacorso, Helio G.; Stradiotto, Mark
Abstract: The new synthetically useful methodology to construct tetrasubstituted trifluoromethylpyrazoles involves halogenation of starting trifluoromethylpyrazoles, and subsequent palladium‐catalyzed Negishi coupling or Buchwald‐Hartwig amination with (hetero)arylzinc chlorides and primary alkylamines.